2017
DOI: 10.1177/1933719116648212
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of HGF and c-MET Interaction in Normal Ovary and Ovarian Cancer: Importance of Targeting c-MET and HGF Interaction

Abstract: Binding of hepatocyte growth factor (HGF) to the c-MET receptor has mitogenic, motogenic, and morphogenic effects on cells. The versatile biological effects of HGF and c-MET interactions make them important contributors to the development of malignant tumors. We and others have demonstrated a therapeutic value in targeting the interaction of c-MET and HGF in epithelial ovarian cancer (EOC). However, both HGF and c-MET are expressed in the normal ovary as well. Therefore, it is important to understand the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 90 publications
(169 reference statements)
0
26
0
Order By: Relevance
“…c-Met is a HGF receptor that is expressed in epithelial cells. In ovarian cancer cells, c-Met is highly expressed and its overexpression is associated with adverse prognosis [ 10 , 19 ]. In the present study, we detected the protein levels of HGF and found CAFs produced high levels of HGF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…c-Met is a HGF receptor that is expressed in epithelial cells. In ovarian cancer cells, c-Met is highly expressed and its overexpression is associated with adverse prognosis [ 10 , 19 ]. In the present study, we detected the protein levels of HGF and found CAFs produced high levels of HGF.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs are known to promote tumour development and progression, as well as stimulate metastasis by secreting a variety of factors [ 9 ]. Hepatocyte growth factor (HGF) is one of the growth factors secreted by CAFs, and it stimulates cell proliferation, migration and ECM invasion [ 10 ]. c-Met, as a specific receptor of HGF, is highly expressed in a number of tumour types including ovarian cancer [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It implies that CC-CAFs potentially enhance colorectal cancer metastasis by up-regulation of CD44 whose association with metastasis has been observed in our clinical specimen and orthotopic liver metastatic model. We also investigated the underlying mechanism of pro-tumor effect of CC-CAFs, based on report by Benjamin et al [22], HGF is a major component of cancer associated fibroblasts secretion, and have been showed to promote cancer progression [13, 2325]. However, the mechanism has not decisively investigated in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They promote tumor growth, angiogenesis and the malignant progression of various solid tumor through direct cell–cell contact or by paracrine secretion [8, 9], up-regulation of epidermal growth factor (EGF), interleukin-6 (IL-6), insulin-like growth factor, or hepatocyte growth factor in CAFs has been reported recent years [1012]. Hepatocyte growth factor (HGF) is an important fibroblast secreted protein [13] which binds to Met, a specific receptor expressed in tumor cells and actives downstream signal that mediates development and progression of cancers [14, 15]. It has been reported that HGF/c-Met activation could subsequently result in up-regulation of CD44 expression [16], this implies that possible correlation exists between CAFs and adhesion process, however it has not been elucidated so far.…”
Section: Introductionmentioning
confidence: 99%